Trends of water and sand fluxes in the Yellow River analyzed based on LSTM model prediction - Yan, Peixi; Luo, Haotian; Zheng, Kaiwen (Transactions on Environment, Energy and Earth Sciences, 2024)
The Yellow River, the river with the highest sand content in China, the change in its water-sand flux has a significant impact on the ecological environment and resource management. In this paper, we mainly use the LSTM neural network model to predict the change rule of water and sand flux in the next two years according to the data from 2016 to 2021, and finally draw time series graphs according to the prediction results, we find that the water and sand flux has seasonality and sudden change, according to this characteristic, we formulate the optimal monitoring program for the dynamic change of water and sand flux in the next two years, to reduce the waste of monitoring resources. Mastering the change rule of water and sand flux in the Yellow River can provide a scientific basis for allocating water resources and constructing an ecological environment in the Yellow River.